Perspectivism, Deontologism and Epistemic Poverty. (3rd March 2016) - Lockie, Robert
Abstract : The epistemic poverty objection is commonly levelled by externalists against deontological conceptions of epistemic justification. This is that an "oughts" based account of epistemic justification together with "ought" implies "can" must lead us to hold to be justified, epistemic agents who are objectively not truth-conducive cognizers. The epistemic poverty objection has led to a common response from deontologists, namely to embrace accounts of bounded (perspectival) rationality—subjective, practical or regulative accounts rather than objective, absolute or theoretical accounts. But the bounds deontological epistemologists and their opponents entertain rarely include cultural limitations. This paper considers neo-Vygotskian (contextualised cognition) arguments that we must consider such cultural limits in defending deontologism, and thus that any deontologically motivated perspectivism must be in part a cultural perspectivism. The dangers of strong relativism are flagged and an attempt is made to steer a middle path between this and a parochial anti-rationalist objectivism.